CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.
CRIS-Team Scopus Importer:2020-07-24